Double crystallization behavior in dry-jet wet spinning of cellulose/N-methylmorpholine-N-oxide hydrate solutions - Kim, DB; Lee, YM; Lee, WS; Jo, SM; Kim, BC (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
The structure and resultant mechanical properties of fibers in the dry-jet wet spinning process of cellulose solutions in N-methylmorpholine-N-oxide (NMMO) hydrates were investigated in terms of molecular weight of cellulose, concentration, and hydration number (n) of NMMO hydrate. The value of n had an effect on the crystallization behavior of the cellulose solution system, which influenced the resultant fiber structure. Increasing cellulose concentration and decreasing the value of n retarded crystallization because of the increased interactions between cellulose and NMMO hydrate. Reducing the value of n from 1 to 0.72 produced more highly oriented cellulose fibers. However, incorporating n-propyl gallate, an antioxidant, had little effect on the fiber structure. When n = 0.72 a double crystallization behavior was observed in the fiber spinning process irrespective of molecular weight of cellulose and concentration over the experimental ranges examined. It should be noted that such a double crystallization took place in the absence of foreign additives. The double crystallization behavior was more noticeable when the aspect ratio of spinning nozzle was greater. The double layer structure had a positive effect on the mechanical strength. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: FIBERS; SYSTEM; PHASE